Sub-20 nm LiErF4-Based Upconversion Nanophosphors for Simultaneous Imaging and Photothermal Therapeutics - Hong, A-Ra; Byun, Ji Young; Lee, Kwangyeol; Jang, Ho Seong (AMER CHEMICAL SOC, 2020)
This study reports red-emitting LiErF4:Tm-based upconversion nanophosphors (UCNPs) with small size and high brightness for simultaneous upconversion luminescence (UCL) imaging and photothermal therapeutics. Strong red UCL is realized from LiErF4-based UCNPs by doping Tm3+ into LiErF4 and forming multishells on the LiErF4:Tm core. The ultrasmall LiErF4:Tm UCNPs are facilely synthesized by using rare-earth-oleate precursors and a mixed solvent of oleic acid and 1-octadecene. The size of the ultrasmall LiErF4:Tm(0.3%) UCNPs is finely tuned from 2.8 to 10.4 nm, and LiErF4:Tm(0.3%)/LiGdF4 core/shell (C/S) UCNPs show small sizes ranging from 8.6 to 13.2 nm. Notably, 11.4 nm-sized C/S UCNPs show bright red light. Furthermore, LiErF4:Tm-based core/triple-shell (C/T-S) UCNPs are synthesized, and they show dramatic enhancement of red UCL (similar to 4242-fold enhancement compared with the core under 980 nm excitation and similar to 89-fold and similar to 14-fold enhancement compared with the C/S UCNPs under 800 and 1532 nm excitation, respectively). Besides UCL enhancement, Nd3+ ions doped in the LiErF4:Tm-based C/T-S UCNPs generate heat under 800 nm irradiation, allowing the C/T-S UCNPs to be applied as photothermal therapeutic agents. The ultrasmall (<20 nm) and bright red-emitting LiErF4:Tm-based C/T-S UCNPs have the potential for simultaneous imaging and photothermal therapeutic applications.
Keywords: CONFINING EXCITATION-ENERGY; FACILE SYNTHESIS; NANOPARTICLES; NANOCRYSTALS; LUMINESCENCE; PLATFORM; SURFACE; EMISSION